How do insured deposits affect bank risk? Evidence from the 2008 emergency economic stabilization act - Claudia Lambert; Felix Noth; Ulrich Schüwer (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
This paper tests whether an increase in insured deposits causes banks to become more risky. We use variation introduced by the U.S. Emergency Economic Stabilization Act in October 2008, which increased the deposit insurance coverage from 100,000 to 250,000 per depositor and bank. For some banks, the amount of insured deposits increased significantly; for others, it was a minor change. Our analysis shows that the more affected banks increase their investments in risky commercial real estate loans and become more risky relative to unaffected banks following the change. This effect is most distinct for affected banks that are low capitalized.
Keywords: G21; G28; 330; financial crisis; deposit insurance; bank regulation